Legal Responsibilities of Corporations That Conduct Deeds Pollution Environment Based on Law N0. 32 Of 2009 Concerning Protection and Management Environment - Herawati, Herawati; Simamora, Janpatar; Sidauruk, Jinner (Jurnal Mamangan, 2023)
Based on the results of the discussion above, it can be concluded that Law Number 32 of 2009 concerning Environmental Protection and Management is related to the Job Creation Law, namely Law Number 11 of 2020 concerning Job Creation where the Law has a positive impact on almost all existing laws and policies, because with the enactment of the Job Creation Law. Corporate legal responsibility for environmental pollution is regulated in Law Number 32 of 2009 concerning Environmental Protection and Management. In this framework, the active involvement of the government and the community plays an important role in the process of supervision and law enforcement against companies proven to have polluted. This research aims to enrich understanding of the extent to which the application of environmental law in Indonesia is effective, as well as to examine the potential for strengthening synergies between the government and society in realizing a healthy and sustainable environment. Corporate responsibility is not only limited to financial aspects, but also includes social and environmental dimensions. Therefore, companies are required to comply with applicable legal provisions and take concrete steps to prevent and reduce the negative impact of their business activities on the environment.